SISTEM MANAJEMEN PEMANFAATAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) - kurnia kurnia; rustan santaria; Masmuddin Masmuddin (Kelola: Journal of Islamic Education Management, 2021)
The main problem of this research was the utilization system of school operational fund. This research used qualitative research method to find out the maximum result in the field related to the utilization of school operational fund at sekolah/ madrasah by using management and sociology approaches. The data collection techniques used in this research were observation, interview, and documentation. Then, the researcher asked some questions about the utilization of school operational fund management system by using open instrument namely giving questions or direct interview and using recorder tool. The result of the research shows that: 1) the management system of school operational fund utilization at sekolah Dasar Negeri 29 Bajo is appropriate with the technical guide of school operational fund 2) the management system of school operational fund utilization at Madrasah Ibtidaiyah Swasta 09 Bajo is really appreciated because it is very helpful in school developmentand the honorer payment at madrasah. 3) The differences of the school operational fund utilization is in the the use of the fund based on juknis sekolah Dasar which 100% should be appropriate while Madrasah Ibtidaiyah Swasta is not really ready to follow the rules since the payment of honor was 50% while in sekolah dasar is only 15%. From the book availability must be 20% every year while in Madrasah, it is not a must.